Business Planning : Mud Crab Aquafarm / Juriyati Jaafar ...[et al.] - Jaafar, Juriyati; Rosnan, Noor Ani; Mad Ali, Noor Hasibah; Mohd Azmi, Norasmida (2009)
MUD CRAB AQUAFARM is the one of company which is produce by four local businesswoman come from Pahang and also Kelantan. This business supplies the high quality of crab and the scientific name for it is Scylla Serrata to the customers especially for those who open up the business like restaurant, hotel, or market. The benefit of eating this crab is, it can help the person who have Dengue and release the sicknesses